Differences wellness among students in guidance and counseling major FKIP UHAMKA Early And Year End Year Class - Fatma Nofriza; Dony Darma Sagita (Universitas Negeri Padang, 2018)
The background of this research is the emergence of diverse and confusing behavior between students of UHAMKA phenomenon who stay in first and last term on the major counseling. This study aims to describe differences between them in wellness condition. This research was conducted on the students of the Guidance and Counseling majors, Faculty of Teacher and Education Science in the fisrt and last semester. The population of this study supports 147 people in a group and 197 people in B group. The sample was 177 people in a group and 69 people in B group. Sampling technique used is random sampling that. This research uses quantitative methods of comparative approach. The Data in this research is the normal distribution but not homogeneous so that the applied technique of nonparametric analysis of data with the test method of hypothesis U-test (Mann Whitney). Based on the calculation result of the U-test (Mann Whitney) Obtained Z>observed Ztable(22.574>1.96) the which means H0 rejected. The results of this study concluded that there are differences in the level of wellness between a groups of samples, with the wellness of students who stay in last half is much larger than the Guidance Counseling Major student Who stay in the first half.